Analysis of Students' Errors on the Fraction Calculation Operations Problem - Safriani, Wirda; Munzir, Said; Duskri, M; Maulidi, Ikhsan (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
Students' errors on fraction problems often occur, especially in fraction counting operations. This error shows that the ability of students who do not understand the fraction problems. To overcome these errors, attention from the teacher is needed so that mistakes can be resolved. The purpose of this study is to describe students' errors in the fraction counting operation problem on each indicator, which is related to converting mixed fractions to ordinary fractions, determining fractions of value, and performing fraction addition and subtraction operations. This research is a qualitative descriptive study. The results showed that the majority of students experienced concept errors on each indicator requested in this study. Also, students make other mistakes such as mistakes of principle and carelessness.